Organizational Culture, Transformational Leadership, Work Engagement, and Championing Behavior in East Kalimantan Central Statistics Agencies - Christin Elisabeth Simorangkir; Fajar Apriani; Iman Surya (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
In the context of bureaucracy reform and improving the quality of public services, proactive employee behavior towards change, including championing behavior, is crucial. This study aims to analyze the relationship between organizational culture and transformational leadership in fostering work engagement and championing behavior among employees of the Central Statistics Agency in East Kalimantan Province. The research approach used quantitative methods with path analysis techniques through SPSS 23 and Smart PLS. The research sample consisted of 184 employees of the Central Statistics Agency in East Kalimantan Province. The results of the analysis showed that organizational culture had a positive and significant relationship with work engagement; transformational leadership did not have a substantial relationship with work engagement; organizational culture is positively and significantly related to championing behavior; transformational leadership is positively and significantly associated with championing behavior; championing behavior is positively related to work engagement; and organizational culture and transformational leadership simultaneously positively and significantly associated with work engagement and have an impact on championing behavior. These findings confirm that an adaptive and collaborative organizational culture and transformational leadership play an important role in encouraging work engagement, while championing behavior strengthens employee contributions to organizational change.